Structural Embeddedness and Firms’ Impact on the Technology Standard Setting Process - Song, Zhi-hong; Huo, Feng-jiao; Lee, Dong-mei (Journal of Accounting, Business and Finance Research, 2019)
The extant literatures often focus on the efficiency of standard committees to coordinate conflicts between members and how regulatory capture occurs, thus neglecting the impact of cooperation behaviour on the technology standard setting process. This paper aims to explore how structural embeddedness affects firms’ impact on the technology standard setting process. We construct a network with the national standard data in China’s communications industry in 2000-2017. With 326 firms participating in the standard formulation as the research sample, we use the negative binomial regression method to explore the relationship between structural embeddedness of technology sponsors and the impacts on the technology standard setting process. We find that while there is an inverted U-shaped relationship between the number of direct collaborators and firms’ impacts on the technology standard setting process, the structural holes positively affect firms’ impacts on the technology standard setting process. The conclusions obtained from this paper have important managerial implications for firms participating the technology standard setting processes.